Good evening ,
Answer:
In this case the dilation is a reduction (as you can see the image triangle is smaller than the original triangle)
and also the scale factor = OA’/OA = 2/6 = 1/3
since -1 < 1/3 < 1 then it’s a reduction.
Step-by-step explanation:
Look at the photo below for more details (notice OA’ and OA).
________________________________________________
:)
Step-by-step explanation:
f(x) = 9 * 81^x
When x = -1/2,
f(-1/2) = 9 * 81^(-1/2) = 9 * (1/9) = 1.
Answer:
![\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x} = \frac{x - 6}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7Bx%20-%206%7D%7B4%2Ax%7D)
Step-by-step explanation:
We have the expression:
![\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D)
The first thing we want to do, is to have the same denominator in both equations, then we need to multiply the first term by (2/2), so the denominator becomes 4*x
We will get:
![(\frac{2}{2} )\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x} = \frac{4*x - 4}{4*x} - \frac{3*x + 2}{4*x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B2%7D%20%29%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7B4%2Ax%20-%204%7D%7B4%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D)
Now we can directly add the terms to get:
![\frac{4*x - 4}{4*x} - \frac{3*x + 2}{4*x} = \frac{4*x - 4 - 3*x - 2}{4*x} = \frac{x - 6}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B4%2Ax%20-%204%7D%7B4%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7B4%2Ax%20-%204%20-%203%2Ax%20-%202%7D%7B4%2Ax%7D%20%20%3D%20%5Cfrac%7Bx%20-%206%7D%7B4%2Ax%7D)
We can't simplify this anymore
Answer:
C. = 69.5
Step-by-step explanation:
The median or the average between 80 and 59 is 69.5
Hope this helps! :)